Why do high‐performing school leavers aspire to occupations atypical of their qualification? - Eberhard, Verena [Verfasser]; Schnitzler, Annalisa [Verfasser]; Mentges, Hanna [Verfasser] (My University, 2022)
„In Germany, the dual system of vocational education and training is an attractive alternative to tertiary programmes for school leavers with a higher education entrance certificate (HEEC). Most adolescents with this qualification opt for training occupations where the majority of apprentices hold an HEEC (e.g., bank clerk). This decision seems sensible considering that such training occupations are difficult for people with lower school‐leaving certificates to access and promise better career outcomes. Nevertheless, some adolescents with an HEEC enter occupations that are not typical of their school‐ leaving qualification. This article examines under which circumstances adolescents with an HEEC aspire to training occupations atypical of their level of education and thus accept lower career outcomes. Following the rational choice paradigm, we expect differences in perceived benefit and probability of success between school leavers with an HEEC opting for HEEC occupations as opposed to non‐HEEC occupations. Using data from the 2018 DZHW Panel Study of German School Leavers With an HEEC, our logistic regression models show that the individuals’ self‐assessed strengths and their occupational goals explain why they aspire to training occupations atypical of their qualification. Contrary to our assumption, adolescents from academic families are not less likely to aspire to non‐HEEC occupations. “ (authors’ abstract; BIBB-Doku)
Keywords: P 2.1 Schulabgänger; P 2.1.5 Fachhochschul- und Hochschulreife; L 5 Beratung & Orientierung; 370; Schulabgänger; Abiturient; Studienberechtigung; Ausbildungswahl; Ausbildungsplatzwahl; Einflussfaktor; Bildungsaspirationen; Segmentation